(untitled) (Research, Society and Development, 2022)
Internal communication helps organizations to develop their processes and services more efficiently, aligning strategies that help increase the competitiveness of companies in the market. Therefore, this research aims to analyze how internal communication can contribute to the improvement of services provided by a Vehicle Dealer in Aracaju/SE. The methodology consists of an exploratory qualitative-quantitative research that carried out the application of a semi-open questionnaire to the company’s employees, which was applied to 18 employees. The results indicated that the majority of employees consider the internal communication bad and that there is a failure between the sectors, showing that it is still necessary for the company to invest in improving the communication process. However, it was noted that the interviewees considered that the company’s communication with the customer is excellent, which favors the growth of customer satisfaction.